2021
DOI: 10.15587/1729-4061.2021.233606
|View full text |Cite
|
Sign up to set email alerts
|

Short-term fire forecast based on air state gain recurrence and zero-order brown model

Abstract: Possibilities of parameterization of the zero-order Brown model for indoor air forecasting based on the current measure of air state gain recurrence are considered. The key to the zero-order parametric Brown forecasting model is the selection of the smoothing parameter, which characterizes forecast adaptability to the current air state gain recurrence measure. It is shown that for effective short-term indoor fire forecast, the Brown model parameter must be selected from the out-of-limit set defined by 1 and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 31 publications
0
29
0
3
Order By: Relevance
“…1, 2, are explained by the various possibilities of modifying Brown's zero-order model to carry out IF STF. A known modification reported in [38] indicates that the unclustered set for the smoothing parameter makes it possible to predict non-stationary current measures of recurrence of increments of the AEP state vector quite effectively. For example, the investigated errors related to STF for materials with different rates of ignition are about an order of magnitude smaller for the unclustered set of the exponential smoothing parameter compared to the classical set.…”
Section: Discussion Of Results Of Studying the Modification Of Brown's Zero-order Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…1, 2, are explained by the various possibilities of modifying Brown's zero-order model to carry out IF STF. A known modification reported in [38] indicates that the unclustered set for the smoothing parameter makes it possible to predict non-stationary current measures of recurrence of increments of the AEP state vector quite effectively. For example, the investigated errors related to STF for materials with different rates of ignition are about an order of magnitude smaller for the unclustered set of the exponential smoothing parameter compared to the classical set.…”
Section: Discussion Of Results Of Studying the Modification Of Brown's Zero-order Modelmentioning
confidence: 99%
“…The subject of the research was the dynamics of STF errors, characterized by the exponentially smoothed (a parameter of 0.4) values for the current absolute and average STF errors. The materials used, the research methods and the procedure are described in detail in work [38]. We studied the accuracy of IF STF one step in advance using the proposed modification of Brown's zero-order model and exponential smoothing based on experimental data.…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [15], it is shown that to improve the quality of F of irreversible PPs, the classical set for the smoothing parameter is advisable to expand. Based on this, paper [41] reports a study into the quality of F of FP based on the use of ZOBM for the smoothing parameter from the classical and beyond-the-limit sets. It is confirmed that in the case of a beyond-the-limit set, the F quality indicators increase.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%